ANALISIS PERILAKU PENGGUNA WEBSITE SISTEM INFORMASI AKADEMIK MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Permadi, Asep; Irawati, Tri; Widada, Bebas (STMIK Sinar Nusantara, 2023)
Veteran Bantara University has been implemented a website which includes an academic information system. It aims that all the students’ can access the information by online anytime and anywhere. This website-based academic information system implemented by Veteran Bantara University has been upgrade in 2019. By this condition, all the students can use the new system conveniently. According to this problem, it needs to analyze the behavior of users of the new academic information system using the Technology Acceptance Model (TAM). The purpose of this research is to analyze the behavior of website users at veteran Bantara University using the technology acceptance model method. The methodology analysis the researcher uses Partial Least Squares (PLS) analysis and it develops an application to test the technology acceptance model method with the PHP programming language. The result of this result showed that there are five from six hypothesizes which have significant positive effect on the dependent variable with an effect value of 0,653 (65,3%), 0,447 (44,7%), 0,677 (67,7%), 0,520 (52,0%), 0,605 (60,5%) and the other shows significant negative effect on the value of 0,170 (17,0%).